2004
DOI: 10.1210/er.2003-0024
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Secretion and Action: Evidence for Discrete Receptors for the Carboxyl-Terminal Region and Related Biological Actions of Carboxyl-Terminal Ligands

Abstract: PTH is a major systemic regulator of the concentrations of calcium, phosphate, and active vitamin D metabolites in blood and of cellular activity in bone. Intermittently administered PTH and amino-terminal PTH peptide fragments or analogs also augment bone mass and currently are being introduced into clinical practice as therapies for osteoporosis. The amino-terminal region of PTH is known to be both necessary and sufficient for full activity at PTH/PTHrP receptors (PTH1Rs), which mediate the classical biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(184 citation statements)
references
References 412 publications
3
169
0
12
Order By: Relevance
“…9 We disclose the limit of not having measured PTHrP but the low PTH levels observed in our hypercalcemic patients are consistent with PTHrP elevation since the IRMA assay we used for PTH evaluation does not cross-react with PTHrP. 9,17,18 Out of 151, two patients (1.3%), however, had elevated levels of both serum calcium and PTH suggesting primary hyperparathyroidism. Hyperparathyroidism is frequent in the aged population, 20 thus the association Disordered calcium metabolism and prognosis M Tucci et al with prostate cancer is not expected to be rare even if precise estimates are not presently available.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…9 We disclose the limit of not having measured PTHrP but the low PTH levels observed in our hypercalcemic patients are consistent with PTHrP elevation since the IRMA assay we used for PTH evaluation does not cross-react with PTHrP. 9,17,18 Out of 151, two patients (1.3%), however, had elevated levels of both serum calcium and PTH suggesting primary hyperparathyroidism. Hyperparathyroidism is frequent in the aged population, 20 thus the association Disordered calcium metabolism and prognosis M Tucci et al with prostate cancer is not expected to be rare even if precise estimates are not presently available.…”
Section: Discussionsupporting
confidence: 53%
“…NTX was measured using a commercial kit (Osteomark, OrthoClinical Diagnostics, Rochester, NY, USA), plasma CgA was measured using an enzyme-linked immunosorbent assay kit (Dako, Glostrup, Denmark) serum PTH (intact molecule) was measured by an immunoradiometric assay (Nichols, San Juan Capistrano, CA, USA) that does not cross-react with PTHrP. 17,18 Measuring ranges, minimum detectable concentrations, intra-and interassay coefficients of variation were as follows: NTX 30-3000 nM, 20 nM, 4.4 and 6.9%; CgA 5-650 U l À1 , 2 U l À1 , 4.7 and 5.6%; PTH 2.5-2000 pg ml À1 , 2.1 pg ml À1 , 4.1 and 4.9%.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Since the hPTH-fragments (53-84) and (28-48) including hPTH-(7-84) do not have an effect per se on cAMP synthesis, the suppressive effect may be the result of an indirect regulation of the type I PTH/PTHRP receptor by the action of C-PTH-fragments on the C-PTH receptor. Binding experiments have shown that Cterminal PTH peptides can bind specifically and is equally displaced by PTH-(7-84) and by PTH-(1-84), but only partially displayed by PTH-(1-34) [19][20][21]. Binding data specific for PTH-(53-84) have been demonstrated [22].…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroid hormone-related protein (PTHrP) is a PTH-like calcitropic hormone, a growth factor and regulator of development (Murray et al, 2005). Tumor-derived PTHrP appears to be a crucial component of a chain of signalling events among cells of the bone microenvironment that facilitates both the destruction of bone and the growth of tumor cells (Guise et al, 1996;Thomas et al, 1999, Kozlow& Guise 2005.…”
Section: Parathyroid Hormone In Invasive Breast Cancer 311 Role Of mentioning
confidence: 99%